Assessment of Multiplex Digital Droplet RT-PCR as a Diagnostic Tool for SARS-CoV-2 Detection in Nasopharyngeal Swabs and Saliva Samples. (2nd January 2021) - Cassinari, Kévin; Alessandri-Gradt, Elodie; Chambon, Pascal; Charbonnier, Françoise; Gracias, Ségolène; Beaussire, Ludivine; Alexandre, Kevin; Sarafan-Vasseur, Nasrin; Houdayer, Claude; Etienne, Manuel; Caron, François; Plantier, Jean Christophe; et al.
Abstract: Background: Reverse transcription-quantitative PCR on nasopharyngeal swabs is currently the reference COVID-19 diagnosis method but exhibits imperfect sensitivity. Methods: We developed a multiplex reverse transcription-digital droplet PCR (RT-ddPCR) assay, targeting 6 SARS-CoV-2 genomic regions, and evaluated it on nasopharyngeal swabs and saliva samples collected from 130 COVID-19 positive or negative ambulatory individuals, who presented symptoms suggestive of mild or moderate SARS-CoV2 infection. Results: For the nasopharyngeal swab samples, the results obtained using the 6-plex RT-ddPCR and RT-qPCR assays were all concordant. The 6-plex RT-ddPCR assay was more sensitive than RT-qPCR (85% versus 62%) on saliva samples from patients with positive nasopharyngeal swabs. Conclusion: Multiplex RT-ddPCR represents an alternative and complementary tool for the diagnosis of COVID-19, in particular to control RT-qPCR ambiguous results. It can also be applied to saliva for repetitive sampling and testing individuals for whom nasopharyngeal swabbing is not possible.